2020
DOI: 10.1089/jayao.2019.0072
|View full text |Cite
|
Sign up to set email alerts
|

Participant Perceptions on a Fitbit and Facebook Intervention for Young Adult Cancer Survivors: A Qualitative Study

Abstract: Purpose: Among cancer survivors, physical activity (PA) is associated with reductions in cancer recurrence, morbidity, and mortality. Most young adult (YA) survivors do not attain adequate PA. Digital modalities, specifically wearable activity monitors with a paired mobile application and private social media group for support offer a promising approach for promoting PA among YAs. We conducted a pilot randomized controlled trial of this intervention. To evaluate its acceptability and perceptions of the interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…27,30,33 Besides the 2 studies that used qualitative approaches exclusively, 20,36 most studies (n = 14) nested the qualitative Cheng et al component in their overall design. Among these studies, 13 used individual interviews to collect data, 20,25,26,[28][29][30][31][32][33][35][36][37][38] 2 used focus groups, 19,34 and 1 used the participants' descriptive comments from the final stage of intervention session. 27 Thirteen studies described the data analysis approach: 5 used content analysis, 20,30,32,37,38 6 used thematic analysis, 19,26,31,[34][35][36] 1 used hermeneutic research data analysis, 33 and 1 used deductive analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…27,30,33 Besides the 2 studies that used qualitative approaches exclusively, 20,36 most studies (n = 14) nested the qualitative Cheng et al component in their overall design. Among these studies, 13 used individual interviews to collect data, 20,25,26,[28][29][30][31][32][33][35][36][37][38] 2 used focus groups, 19,34 and 1 used the participants' descriptive comments from the final stage of intervention session. 27 Thirteen studies described the data analysis approach: 5 used content analysis, 20,30,32,37,38 6 used thematic analysis, 19,26,31,[34][35][36] 1 used hermeneutic research data analysis, 33 and 1 used deductive analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“… 14 The study also found that daily Fitbit step counts of over 12 500 steps would meet commonly promoted physical activity guidelines of over 60 min of activity per day. A similar study by Miropolsky et al 15 on 13 young adult cancer survivors between ages 20 and 39 years suggested a Fitbit device could provide major motivation to engage in physical activity.…”
Section: Background and Significancementioning
confidence: 78%
“…The study also found that daily Fitbit step counts of over 12,500 steps would meet commonly promoted physical activity guidelines of over 60 minutes of activity per day. A similar study by Miropolsky, et al, on 13 young adult cancer survivors between ages 20 and 39 years suggested a Fitbit device could provide major motivation to engage in physical activity 13 .…”
Section: Background and Significancementioning
confidence: 79%
“…Kerner, et al studied one-hundred participants from two schools using Fitbit devices for 8 weeks, along with the Fitbit app. They found using Fitbits can initially encourage adolescents (ages [13][14] to exercise, but the participants were eventually discouraged potentially because Fitbit might be setting unrealistic goals 14 . The non-personalized goal of 10,000 steps per day made participants feel unmotivated and lazy if they did not achieve that goal, which discouraged them from exercising 14 .…”
Section: Background and Significancementioning
confidence: 99%